Effectiveness of Food Barn in Improving Rice Farmers Income - Refa'ul Khairiyakh; Hani Perwitasari; Herdiana Anggrasari (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Food barn is a program created to realize food security at the micro level through the maintenance of food availability as one implemented in Bantul. This study aims to investigate the implementation of food barn management and the effectiveness of food barn in increasing rice farmers’ income. Located at Timbul Asih Food Barn, Bantul Regency, this study collected the respondents involving ten rice farmers who were members of the food barn using a census system, and 35 non-members using random sampling. The implementation of food barn management was analyzed descriptively, while the effectiveness of the food barn program in increasing the farmers’ income was analyzed using an independent t-test. The results reveal that Timbul Asih Food barn in Bantul Regency has applied five management functions; however, the addition of members is necessary for the dynamic operation of Timbul Asih Food Barn. The t-test analysis indicates that there is no significant income difference between the member farmers and those who were not members of the food barn. This implies that the presence of food barn is not yet effective in increasing the income of its members